2021
DOI: 10.1155/2021/2767012
|View full text |Cite
|
Sign up to set email alerts
|

Very Elevated IgE, Atopy, and Severe Infection: A Genomics-Based Diagnostic Approach to a Spectrum of Diseases

Abstract: Elevated IgE has been long recognized as an important clinical marker of atopy but can be seen in a myriad of conditions. The discovery of autosomal dominant STAT3 deficiency marked the first recognition of hyper-IgE syndrome (HIES) and the first primary immunodeficiency linked to elevated IgE. Since then, genomic testing has increased the number of defects with associated mutations causing hyper-IgE syndrome and atopic diseases with FLG, DOCK8, SPINK5, and CARD11, among others. A spectrum of recurrent infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…We examined the SNPs with the highest odds ratio (OR), and observed rs6696218 to have the highest OR (21.45) with p = 8.61e-05, the effect size of which was overestimated. This genetic mutation is located in LYST, previously showing an association with markedly elevated IgE and severe atopic dermatitis in a case report for a 6-year-old male patient (Chin et al, 2021). Furthermore, we checked the SNPs showing genome-wide significant association with AD as reported in Paternoster et al, 2015, and identified the most significant SNPs to be rs61175833 (p=1.947e-05), which is located in the intergenic region with the nearest protein coding gene being SLC1A3.…”
Section: The Genetic Risk Score Of Ad Was Low-to-medium and Associate...mentioning
confidence: 88%
“…We examined the SNPs with the highest odds ratio (OR), and observed rs6696218 to have the highest OR (21.45) with p = 8.61e-05, the effect size of which was overestimated. This genetic mutation is located in LYST, previously showing an association with markedly elevated IgE and severe atopic dermatitis in a case report for a 6-year-old male patient (Chin et al, 2021). Furthermore, we checked the SNPs showing genome-wide significant association with AD as reported in Paternoster et al, 2015, and identified the most significant SNPs to be rs61175833 (p=1.947e-05), which is located in the intergenic region with the nearest protein coding gene being SLC1A3.…”
Section: The Genetic Risk Score Of Ad Was Low-to-medium and Associate...mentioning
confidence: 88%
“…This gene encodes CD45 and functions as a signalling gatekeeper in T-cells. Tt is reported that this gene is associated with infection and immune deficiencies [22]. PTPRC and COMMD10 of coding and splicing variants are involved in memory T cell differentiation, and genetic variation controlling T helper cell subsets with crucial roles in protection against infection and susceptibility to autoimmune disease [23].…”
Section: Discussionmentioning
confidence: 99%
“…While the ideal time to perform an oral challenge for FPIES has not been systematically neoplastic, or immunodeficiency diseases, in addition to allergic diseases. 34 Elevation of total IgE, that is, serum total IgE, is neither a useful nor an exclusive marker for diagnosing allergic sensitization, 35 as was agreed by experts. Total IgE is a type of antibody that is associated with allergic responses, but its elevation does not definitively indicate the presence of a specific allergy.…”
Section: Diagnostic Testsmentioning
confidence: 99%